Sickness presenteeism: measurement and management challenges. Issue 3 (4th March 2018) - Whysall, Zara; Bowden, James; Hewitt, Michael
Abstract: Since work can be restorative to health, attending work when unwell should not be viewed as an inherently negative phenomenon. However, the functional benefits are likely to depend on the health condition, and the psychosocial quality of the work provided. The current study used a workforce survey to explore differences in the pattern of presenteeism and absenteeism by health condition, the association of psychosocial work factors with presenteeism compared to absenteeism, and their interaction to predict health. Findings indicate that instead of substituting absenteeism for presenteeism, the two tend to coincide, but the balance differs by health condition. Presenteeism is more likely to occur in poorer psychosocial environments, reinforcing the importance of ensuring work is designed and managed in ways that are beneficial rather than detrimental to health. The findings also highlight the methodological importance of differentiating between the act and impact of presenteeism in future research and practice. Practitioner Summary: Effective management of work-related health requires that practitioners manage both sickness absence and presence together, since employees tend to fluctuate between the two when unwell. Interventions should be tailored to the specific health concern, paying particular attention to the psychosocial environment in enabling employees to continue working without exacerbating health.